1970
DOI: 10.1002/oms.1210040161
|View full text |Cite
|
Sign up to set email alerts
|

ELectron-impact studies in medicine and biochemistry—II: The mass spectra of the alkaloids fromCissampelos ovalifolia D.C.

Abstract: The mass spectra of some new alkaloids extracted from Cissampelos ovalifolia are discussed. The compounds are shown to be tertiary bis-benzyl isoquinoline bases of an unusual type possessing a p-xylyl moiety. Some information about the relative positions of hydroxyl and methoxyl substituents in the macrocyclic ring system is also obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1978
1978
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…Besides the molecular ion at m/z 592 and the base peak at m/z 488, formed by the expulsion of C 8 H 8 , the p-xylyl moiety, ring C (M C ž 104), characteristic for this class of alkaloids, 6 the spectrum was identical with that of warifteine. 1 A primary goal of this study was to determine the location of the phenolic and methoxyl substituents of alkaloid 1, so that its complete structure would finally be known. The initial structural studies of 2 3 tentatively placed the free phenolic group of 2 on C-8, in part by acquiring 60 MHz 1 H NMR of both 2 and the analogue dimethylwarifteine.…”
Section: Resultsmentioning
confidence: 99%
“…Besides the molecular ion at m/z 592 and the base peak at m/z 488, formed by the expulsion of C 8 H 8 , the p-xylyl moiety, ring C (M C ž 104), characteristic for this class of alkaloids, 6 the spectrum was identical with that of warifteine. 1 A primary goal of this study was to determine the location of the phenolic and methoxyl substituents of alkaloid 1, so that its complete structure would finally be known. The initial structural studies of 2 3 tentatively placed the free phenolic group of 2 on C-8, in part by acquiring 60 MHz 1 H NMR of both 2 and the analogue dimethylwarifteine.…”
Section: Resultsmentioning
confidence: 99%
“…Chemical and mass spectral analysis of these bases (Snedden, Parker & Gorinsky, 1970), referred to as warifteine (I), methylwarifteine (II) and dimethylwarifteine (III) (Fig. 1), have been made and the crystal structure analyses of (II) (this paper) and (III) (Borkakoti & Palmer, 1978) have been successfully completed.…”
Section: Introductionmentioning
confidence: 99%
“…The alkaloid cissampereine isolated from the related plant Cissampelos pareira Linn., and characterized by Kupchan, Kubota, Fujita, Kobayashi, Block & Telang (1966) is isomeric with methylwarifteine. Dimethylwarifteine has been shown by Snedden et al (1970), on the basis of melting point and CH3 0 R4 R3 ~C NMR spectra, to be identical with O-methylcissampereine. Against human carcinoma cells of the nasopharynx in cell culture, (II) has shown significant and reproducible inhibitory activity (Kupchan, Patel & Fujita, 1965).…”
Section: Introductionmentioning
confidence: 99%
“…Chemical and mass spectral studies (Snedden, Parker & Gorinsky, 1970) have shown DMW to be identical with O-methylcissampereine, extracted from the related plant Cissampelos pareira Linn. (Kupchan, Patel & Fujita, 1965).…”
Section: Introductionmentioning
confidence: 99%